Vejrforholdene i Landbrugsaaret 1905—1906. (Fra 1. Oktober 1905 til 30. September 1906.) - Willaume-Jantzen, V. (Tidsskrift for Landøkonomi, 2018)
Vejrforholdene i Landbrugsaaret 1905—1906. (Fra 1. Oktober 1905 til 30. September 1906.)